New Record of Euryhaliotrema cardinale Kritsky & Justine, 2012 and Euryhaliotrema seyi Kritsky, 2012 (Monogenoidea: Dactylogyridae) from Lutjanid Fishes in Iraqi Marine Waters - Ali A.R. Al-Darwesh; Atheer H. Ali (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2025)
Parasitological examination of three species of marine fishes: Blackspot snapper Lutjanus ehrenbergii (Peters), Dory snapper L. fulviflamma (Forsskål) and L. indicus Allen, White & Erdmann (all Lutjanidae, Snappers); caught from Iraqi marine waters, Arabian Gulf during 2024. All these fishes are harboured the same dactylogyrid monogenoid which identified as Euryhaliotrema seyi Kritsky, 2012. Lutjanus ehrenbergii and L. fulviflamma also harboured Euryhaliotrema cardinale Kritsky & Justine in Kritsky, 2012 which considered this record in a new geographical area (Arabian Gulf). The illustrations of whole mount specimens for E. cardinale and E. seyi are given for the first time. This report represents the second work on monogenoids from lutjanid fishes in Iraq.